Akkermansia muciniphila ameliorates chronic kidney disease interstitial fibrosis via the gut-renal axis. (January 2023) - Pei, Tingting; Hu, Rong; Wang, Fujing; Yang, Sixia; Feng, Haitong; Li, Qiye; Zhang, Jiaxing; Yan, Shihua; Ju, Liliang; He, Zhuoen; Han, Zhongxiao; Yang, Aicheng; et al.
Abstract: Context: Chronic kidney disease (CKD) affects approximately 10% of the global population. The abundance of Akkermansia muciniphila (AKK) is significantly reduced in CKD patients. Objective: This study investigated the effects of AKK bacteria on kidney damage and the renal interstitium in rats with CKD. Materials and methods: CKD model 5/6 nephrectomy rats were used. CKD rats were supplemented with AKK (2 × 10 8  cfu/0.2 mL) for 8 weeks. Results: AKK administration significantly suppressed epithelial–mesenchymal transition (EMT), and high-throughput 16S rRNA pyrosequencing showed that AKK supplementation restored the disordered intestinal microecology in CKD rats. AKK also enhanced the intestinal mucosal barrier function. AKK may regulate the intestinal microecology and reduce renal interstitial fibrosis by enhancing the abundance of probiotics and reducing damage to the intestinal mucosal barrier. Conclusion: The results suggest that AKK administration could be a novel therapeutic strategy for treating renal fibrosis and CKD. Highlights: We found that Akkermansia muciniphila improved renal function in rats with chronic kidney disease. Akkermansia muciniphila restores disturbed gut microbiome in rats with chronic kidney disease. Akkermansia muciniphila improves the intestinal mucosal barrier and the level of inflammation in the body. Akkermansia muciniphila improves interstitial fibrosis in chronic kidney disease.